Essential guide to operations management : Concepts and case notes - Bamford, David R.; Forrester, Paul; Reid, Iain (New York : Routledge, 2023)
"The revised and updated second edition of the popular and practical guide to contemporary operations management - now featuring a new chapter on managing sustainable supply networks. The Essential Guide to Operations Management explores fundamental operations management principles, and shows how they are applied in real life situations in both the services and manufacturing sectors. It adapts a strategic stance by providing a framework for effective decision-making: determining operations strategies; through designing processes, products and work organizations; managing change through effective project management and technology transfer; exploring contemporary approaches to operations planning and control; and then managing quality and improvement strategies. As such it addresses the needs of practising managers, postgraduate MBA and MSc students, and final year undergraduates on advanced operations management elective courses. The Essential Guide to Operations Management: Concepts and Case Notes, second edition, is supported by updated case studies throughout and online support materials for lecturers"--
Includes bibliographical references and index.
Keywords: Production management; Process improvement; Quality management; Production planning